Development Communications Protocol for Networks Han in Smartgrids [Desarrollo de Protocolo de Comunicaciones Para Redes Han en Smartgrids] - Kaschel-Carcamo, H; Viera-Riquelme, E (Universidad de Tarapaca, 2017)
The present research work shows the development and implementation of a communications protocol of superior layers, which considers the layers session, presentation and applications, which will be transported through any Ethernet frame. This protocol has the primary objective to monitor and control the communication of the nodes belonging to the HAN network (SmartGrids) in a non-invasive physical layer level, using existent data networks where the proposed protocol will co-exist. This work will begin with a brief definition of the SmartGrids and HAN networks concept, to go on with an explanation of the theoretical development of the protocol, and ending with the implementation and brief traffic analysis which will show the functioning of the protocol. © 2017, Universidad de Tarapaca. All rights reserved.